(3GdeSjM GdefJXQ hfgGjI GdYGde (B/s - (3WhjdI , YHO GdhgGH YHO GdSdGes ((3GdbGgQI (B:s (3OGQ GdSdGe ddWHGYI hGdfTQ hGdJhRjY hGdJQLeI ,s, 2013)
(3jJfGhd gPG GdcJGH HGdHMK hGdOQGSI hGdJMbjb ehVhYG egeG JfGhdJg LejY GdTQGFY GdSeGhjI CdG hgh ehVhY bjGe GdSGYI heG jMjW Hg ef aJf hedGMe, dNQhL GdOGHI, hWdhY GdTeS ef eZQHgG, hZjQgG ef GdaJf hbO LGA cJGHfG gPG djJfGhd Pdc GdehVhY HTcd Ydej eNJda, MjK YbO OQGSI ebGQfI Hjf eG LGA aj cJH GdYgOjf GdbOje hGdMOjK, hHjf eG LGA aj GdbQBf hGdSfI GdfHhjI GdUMjMI eY YQV hLgI fXQ cd edI ef Gdedd ef GdeUGOQ hGdeQGLY GdeYJeOI, eY ELQGA ehGRfI hebGQfI YdejI JhVM GdELGHI GdUMjMI dcd eG jLhH aj NdO GdEfSGf Yf gPG GdehVhY, hbO JfGhd GdcJGH HGdHMK hGdJMdjd JafjO CHGWjd heRGYe Cgd GdcJGH aj JfHDGJge HehYO fgGjI GdYGde hJGQjN YhOI GdSjO GdeSjM, heG jJYdb HGdeSjM GdOLGd, hcja Jchf GdehGLgI Hjfg hHjf GdeSjM GdefJXQ, hcja jfJXQ GdjghO hGdfUGQi hGdeSdehf GdeSjM GdefJXQ GdPj Sha jCJj aj BNQ GdReGf djOeQ CYOGA Gddg hjYdj cdeJg, hjhVM EJaGb GdeSdejf hGdfUGQi Ydi Cf gPG GdQLd gh GdeSjM GHf eQje, hdcfge jNJdahf aj ehYO fRhdg hcjajI gPG GdfRhd ajhVM HeG dG jOY eLGdG ddTc YOe UMI cdGe Cgd GdcJGH hJfHDGJge, heOi UMI hhVhM eG LGA Hg GdbQBf GdcQje hGdSfI GdfHhjI GdUMjMI(B. s
Keywords: (3GdeSjM GdOLGds; (3GdSeYjGJs -- (3GdeSjM GdefJXQ s